Manajemen Ekosistem Pesisir Pulau-Pulau Kecil Untuk Ekowisata Berkelanjutan Di Pulau Saparua - Kaya, Ivonne R.G.; de Lima, Fildo; Kaya, Manuel; Matinahoru, Johan M. (MAKILA, 2020)
Saparua as small island rich in coastal natural resources. Main coastal ecosystem are mangrove, seagrass beds, coral reefs and sandy beach. Coastal ecosystem also has an important role in ecotourism environment services to improve the communities economy and must be managed sustainably. This paper aimed to identifying potential small islands coastal areas as a tourist destination and planned management to sustainable ecotourism used SWOT analysis. Ecotourism was sustained in small islands can be conducted integrally through 14 management strategy to tourism industry which economic, social and environmental dimension. Ecotourism coastal area management of small islands should be done in coordination with the agrosilvofishery.